Financial Viability Assessment of Intermediate Waste Treatment Facilities in South Service Area of DKI Jakarta - Rizal Riyadi; Tjahjo Tri Hartono; Mas Davino Sayaza (Universitas Ibn Khaldun Bogor, 2025)
This study evaluates the economic feasibility of developing Intermediate Waste Treatment Facilities (ITFs) utilizing Waste-to-Energy technology in Jakarta's South Service Area. A comparative analysis was conducted using two scenarios: conventional landfill management versus ITFs implementation at two potential locations—Pesanggrahan (South Jakarta) and Sukapura (North Jakarta). The research employed secondary data analysis over one month in August 2021, utilizing financial indicators including Net Present Value (NPV), Internal Rate of Return (IRR), and Benefit Cost Ratio (BCR). Environmental and social externalities were integrated into the economic assessment. Results demonstrate that conventional landfill approaches yield negative present value of IDR 5.24 billion, indicating financial unsustainability. Conversely, WtE technology scenarios show positive economic viability: Pesanggrahan achieves NPV of IDR 441 million (IRR 12.12%, BCR 1.08), while Sukapura demonstrates superior performance with NPV of IDR 1.25 billion (IRR 16.15%, BCR 1.23). The findings establish clear economic justification for transitioning from disposal-based to resource recovery systems, with industrial zone locations offering strategic advantages for ITF development in Jakarta's waste management modernization strategy.